Alternative dispute resolution - David L. Dickinson (IZA World of Labor, 2014)
Alternative dispute resolution procedures such as arbitration and mediation are the most common methods for resolving wage, contract, and grievance disputes, but they lead to varying levels of success and acceptability of the outcome depending on their design. Some innovative procedures, not yet implemented in the real world, are predicted to improve on existing procedures in some ways. But controlled tests of several procedures show that the simple addition of a nonbinding stage prior to binding dispute resolution can produce the best results in terms of cost (monetary and "uncertainty" costs) and acceptability.
Keywords: J5; J52; C9; 330; dispute resolution; arbitration; mediation; risk aversion; optimism